Promoting Statistical Practice and Collaboration in Developing Countries. - Awe, O. Olawale. (CRC Press LLC, 2022)
The book addresses the topics of individual chapters from the perspectives of the historical context, the present state, and future directions of statistical training and practice, so that readers may fully understand the challenges and opportunities in the field of statistics and data science, especially in developing countries.